PENGEMBANGAN MEDIA PEMBELAJARAN MOBILE LEARNING BERBASIS MASALAH DALAM PEMBELAJARAN PPKN DI SMA - Mega Dewi Sinta; Alfiandra Alfiandra; Sri Artati Waluyati (Universitas Sriwijaya, 2019)
Abstract: This study aims to produce mobile learning media based on problems in political culture material that are valid, practical, and have potential effects. The research method used is the development method with the Hannafin and Peck models. Media validation is managed through three experts, namely material experts, media experts, and linguists. Material validation is included in the valid category with an average of 4.1, media validation is classified as valid with an average of 4.3, and language validation is categorized as very valid with an average of 4.0. Practical support by using one to one which was tested on three students with an average of 4.3 included in the very practical category and a small group with an average of 4.4 including very practical categories. In the trial of problem-based cellular learning media learning in 34 students of class XI had the potential to increase student motivation, as evidenced by the learning motivation level of 72.9% included in the high motivation category, so that it corresponds to the interpretation of the 60-80 score interpretation. % is high motivation. Based on these results it shows that problem-based mobile learning media in cultural material are declared valid, practical, and have a potential effect on students' motivation in high school. Key Words: Development, Mobile learning, Problems, PPKn Abstrak: Penelitian ini bertujuan untuk menghasil media pembelajaran mobile learning berbasis masalah pada materi budaya politik yang valid, praktis, dan memipunyai efek potensial. Metode penelitian yang digunakan adalah metode pengembangan dengan model hannafin dan Peck. Validasi media dinilai melalui tiga ahli yakni ahli materi, ahli media, dan ahli bahasa. Validasi materi termasuk dalam kategori valid dengan rerata 4,1, validasi media tergolong valid dengan rerata 4,3, dan validasi bahasa termasuk kategori sangat valid dengan rerata 4,0. Kepraktisan dinilai dengan menggunakan tahap one to one yang diujikan kepada tiga peserta didik dengan rerata 4,3 termasuk dalam kategori sangat praktis dan tahap small group dengan rerata 4,4 termasuk kategori sangat praktis. Pada tahap uji coba media pembelajaran mobile learning berbasis masalah pada 34 orang peserta didik kelas XI mempunyai efek potensial untuk meningkatkan motivasi belajar peserta didik, terbukti dengan tingkat motivasi belajar sebesar 72,9% termasuk dalam kategori motivasi tinggi, karena berdasarkan kriteria interpretasi skor 60-80% adalah motivasi tinggi. Berdasarkan hasil tersebut menunjukkan bahwa media pembelajaran mobile learning berbasis masalah pada materi budaya politik dinyatakan valid, praktis, dan memiliki efek potensial bagi motivasi belajar peserta didik di Sekolah Menengah Atas. Kata kunci: Pengembangan, Mobile learning, Masalah, PPKn